Promoting High Achievement for Disadvantaged Students: Co-Designing a School Self-Evaluation Process Aligned to Evidence of Successful Leadership Practice Across Five English Districts - Maria Cockerill; Tom Grieveson; Stephanie Bingham; Joanne O’Keeffe (Education Sciences)
Equity of education outcomes for all children continues to be a shared goal amongst education leaders, post-pandemic. In England, issues of underachievement are of particular concern in socio-economically disadvantaged regions. Nevertheless, a minority of schools demonstrate high achievement for students from high-poverty backgrounds. This paper reports on the process of co-designing a school self-evaluation tool aligned to seven key indicators which previous research findings suggest, if implemented together, enable school leaders to promote high academic achievement and well-being for all children. Guided by social interdependence theory, successful local school leaders worked collaboratively, supported by education researchers, to develop self-evaluation tools and peer-support structures. Together, they created the ‘High Achievement Review Programme’ (HARP). We discuss the co-design process of HARP, including the developed evaluation tools for schools.